Endothelial Cell Distribution After Flow Exposure With Two Stent Struts Placed in Different Angles - Wang, Zi; Putra, Narendra Kurnia; Anzai, Hitomi; Ohta, Makoto (Frontiers in Physiology, 2022)
Stent implantation has been a primary treatment for stenosis and other intravascular diseases. However, the struts expansion procedure might cause endothelium lesion and the structure of the struts could disturb the blood flow environment near the wall of the blood vessel. These changes could damage the vascular innermost endothelial cell (EC) layer and pose risks of restenosis and post-deployment thrombosis. This research aims to investigate the effect of flow alterations on EC distribution in the presence of gap between two struts within the parallel flow chamber. To study how the gap presence impacts EC migration and the endothelialization effect on the surface of the struts, two struts were placed with specific orientations and positions on the EC layer in the flow chamber. After a 24-h exposure under wall shear stress (WSS), we observed the EC distribution conditons especially in the gap area. We also conducted computational fluid dynamics (CFD) simulations to calculate the WSS distribution. High EC-concentration areas on the bottom plate corresponded to the high WSS by the presence of gap between the two struts. To find the relation between the WSS and EC distributions on the fluorescence images, WSS condition by CFD simulation could be helpful for the EC distribution. The endothelialization rate, represented by EC density, on the downstream sides of both struts was higher than that on the upstream sides. These observations were made in the flow recirculation at the gap area between two struts. On two side surfaces between the gaps, meaning the downstream at the first and the upstream at the second struts, EC density differences on the downstream surfaces of the first strut were higher than on the upstream surfaces of the second strut. Finally, EC density varied along the struts when the struts were placed at tilted angles. These results indicate that, by the presence of gap between the struts, ECs distribution could be predicted in both perpendicular and tiled positions. And tiled placement affect ECs distribution on the strut side surfaces.